Bibliometric Analysis of Environmental, Social and Governance in Finance - Steliana Mocanu; Ionuț Laurențiu Petre; Marilena Potârniche (Berheci); Cristian Stana (Revista de Studii Financiare)
In the last years, when it comes to invest, the investors take into consideration in addition to the company’s financial report, the non-financial report. Environmental, social, and governance (ESG) factors present an increasing interest year by year as it was identified through the present research. The main objective of this paper is to determine the interest of ESG factors in finance. The research method consists in conducting a bibliometric analysis querying the existing documents in the “Web of Science Core Collection” (WoS) database. The query revealed a number of 477 scientific documents that were carried out between 2008 and 2024 that contain both terms „ESG” and “finance” in title, abstract or keywords. The query was made on April 01, 2024 and the results were processed through VOSviewer software. Main findings of the research are that the most documents (31.24%) were included in the Business Finance category of the Web of Science database and that the research confirm the increase of the scientific interest about ESG and finance, year by year. The countries most interested in writing about ESG and finance are China, with 21% of documents, USA (13% of documents) and United Kingdom (12% of documents). In conclusion, in the context of the low number of documents written on this subject (according to WoS database), this paper adds an important status of the authors’ interest in ESG in finance.